Use of N Natural Abundance and N Species Concentrations to Assess N-Cycling in Constructed and Natural Coastal Wetlands - C. Marjorie Aelion; Melissa R. Engle; Hongbo Ma (Applied and Environmental Soil Science)
Natural abundance of N stable isotopes used in combination with concentrations may be useful indicators of N-cycling in wetlands. Concentrations and N signatures of NO3−, NH4+, and sediment organic nitrogen (SON) were measured in two impacted coastal golf course retention ponds and two natural marshes. Limited NO3− was detected in natural site surface water or pore water, but both isotopic signature and concentrations of NO3− in surface water of impacted sites indicated anthropogenic inputs. In natural sites, NH4+ concentrations were greatest in deeper pore water and least in surface water, suggesting diffusion predominates. The natural sites had greater %SON, and N indicated that the natural sites also had greater NH4+ released from SON mineralization than impacted sites. In NO3−-limited systems, neither concentrations nor N natural abundance was able to provide information on N-cycling, while processes associated with NH4+ were better elucidated by using both concentrations and N natural abundance.